Environmental sustainability strategies: Trends, Gaps and Future Directions - Rashmi Shah, (AG Volumes, 2025)
This review examines environmental sustainability strategies with a focus on emerging trends, existing gaps, and future directions at global and national levels, particularly in the Indian context. It discusses key sustainability approaches such as renewable energy transition, sustainable agriculture, circular economy practices, biodiversity conservation, and policy interventions. The study highlights evolving trends including ESG reporting, climate resilience, technology-driven waste management, and supply chain decarbonization. It also identifies critical sustainability gaps related to resources, emissions, policy implementation, skills, and knowledge. Overall, the review emphasizes the need for integrated, technology-enabled, and collaborative strategies to achieve long-term environmental sustainability and ecological balance.